REPRESENTASI MASKULINITAS PADA KARAKTER PEREMPUAN DALAM FILM “KARTINI” KARYA HANUNG BRAMANTYO - Febriani Dillawati; Muhammad Bayu Widagdo; Amida Yusriana (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2023)
Gender is an interesting topic to research to date, especially issues related to women. Patriarchal culture is often associated with problems where women are considered to only have feminine characteristics and men have masculine characteristics. In this way, women's positions are often subordinated and have low roles, functions and positions. Although in general, masculine is a label given to men, masculine can also be addressed to women who have personalities and behave like men's traits. Women can be masculine not in the context of sex but in the context of gender. This study aims to determine the representation of masculinity in female characters in the film